Design Stunting Detection Applications Using Artificial Intelligence on Android Devices - Stania, Ummi Rizki Alfi; Sarosa, Moechammad; Wijayanti, Rieke Adriati (Politeknik Negeri Malang, 2023)
In this era, careful attention is needed to the development and growth of children, so that if there is an abnormality it can be detected as early as possible. One of the main factors that affect the growth and development of children is the nutritional factor. Lack of knowledge about growing children causes parents not to realize if their child has a disorder such as stunting. Stunting must be detected as early as possible so that solutions can be given to prevent it from happening. These problems must be corrected immediately and the development of the child is not disturbed. Therefore we need an application that can detect stunting disorders in children from an early age so that they can be handled quickly and precisely. In making this application, it will detect the child's height and weight through the camera to perform a nutritional check that detects the child is stunted or not. This application uses artificial intelligence or Artificial Intelligence based on android. Weight measurement results will be sent from the weighing system to the application using the Bluetooth address for the connection so that the weight results can be displayed on the application. Height measurement is carried out using the camera in the application which will detect the child's height through an image. The test results show that the stunting detection application is very helpful for parents to observe the growth and development of children without having to use and calculate children's nutritional problems manually.